Literature Review: High Intensity Interval Training Meningkatkan Kebugaran Jasmani dan Sosial Status Pada Orang Dewasa Gaya Hidup Pasif - Daulay, Dio Alif Airlangga; Vigriawan, Gosy Endra; Sidik, Rizky Muhammad; Utami, Try Setyo; Pratama, Henri Gunawan (Institut Teknologi Bandung, 2024)
WHO recommendations (2020) advise adults to do moderate intensity physical activity for 150-300 minutes (40-60% of Maximum Heart Rate) or high intensity physical activity for 75-150 minutes (60-85% of Maximum Heart Rate ) ) per week to maintain and improve fitness. However, often obstacles such as